Reflection on Uprooting Penury in the Creative Programs of Mahatma Gandhi - Paswan, Madan (Recent Research in Science and Technology, 2011)
The fact that Poverty is a bane that checks the growth of any to any developing nation as well as and hinder her progress is now well established. It is rightly stated that India is a rich country whose inhabitants are poor. In fact the age-old problem of Poverty has stricken more than half of IndiaÃ¢â‚¬â„¢s population.Ã‚Â Mahatma Gandhi who is also known as the father of nation has tackled this malady with his Sarvodaya program which was focused chiefly on the rural development. This paper tends to throw light on the reflections of Mahatma Gandhi on Poverty elimination through his Sarvodaya program and other related thoughts on cottage industries.Ã‚Â